Self-assembly of phthalocyanines on quartz crystal microbalances for QCM liquid sensing applications - Erbahar, Dilek D.; Harbeck, Mika; Gumus, Gulay; Gurol, Ilke; Ahsen, Vefa (Elsevier Science Sa, 2014)
After their widespread use in gas sensors, phthalocyanines are applied as sorption matrices for quartz crystal microbalance (QCM) sensors in liquid phase, as well. In order to enhance sensor performance, the application of ultrathin Pc films is envisaged. In this work, QCM liquid sensors functionalized in a self-assembly process with phthalocyanines are proposed and evaluated for the first time. An asymmetric tetra substituted nickel phthalocyanine having a thiol linker group to covalently attach to the gold electrode of the QCM and three hexyloxy groups was synthesized. The sensor is assessed in its sensing characteristics in water using selected organic compounds. The sensor responses are fast and recovery after analyte exposure is quick. Detection limits for organic compounds down to sub-ppm levels can be reached. The results demonstrate that the application of phthalocyanines as self-assembled monolayers is very effective to obtain high performing QCM liquid sensors. Besides, layers of alkyloxy substituted phthalocyanines have been previously found unsuitable for the use with the QCM in liquids due to the low adhesion of the Pc layer to the transducer. Thus, the covalent attachment is an excellent way to expand the list of available phthalocyanines as sensitive compounds for such sensors in liquids. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Phthalocyanine; Self-assembled monolayer (SAM); Quartz crystal microbalance (QCM); Chemical sensor; Liquid sensing